Intensionality and Truth - Hugly, Philip. author. aut Link
XII, 433 p.
Keywords: Prior's view on intensionality and truth is based on the principle that sentences never name, that what sentences say cannot be otherwise signified, that a sentence says what it says whatever the type of its occurrence, and that sentential quantification is neither eliminable, substitutional, nor referential. The text defends each of these principles.